A robot-driven automatic scribing method via three-dimensional measurement sensor - Luo, Hua; Zhang, Ke; Li, Ruifeng; Liang, Peidong; Li, Zhongwei (Frontiers in Physics, 2022)
The evaluation of the complex workpiece allowance and the scribing the datum line now extremely rely on manual operation. The manual operation is time-consuming and prone to misjudgment, and has a large blind area. To solve these problems, the robot-driven automatic scribing via three-dimensional (3D) measurement sensor method (RAS3DM) is proposed. In this study, we solve the key technology of calibrating the rigid transformation between the 3D measurement coordinate system and laser scribing coordinate system. And a fast and accurate multiple coordinate systems calibration and unification method is proposed, a fixed calibration target and a mobile calibration target are designed. Hence, a structured-light 3D shape measurement sensor driven by an industrial robot with six-degree of freedom (6-DOF) is utilized to obtain the complete 3D shape of the complex workpiece automatically, and then by comparing the 3D measurement result and the standard CAD model, the laser scribing equipment can automatically scribe the mechanical processing datum line to assist further processing. The experiment results illustrate that the proposed method is accurate and efficient: the complex workpiece allowance evaluation and scribing time is about 5 times faster than that of manual operation, and the scribing accuracy is 0.15mm, which can effectively solve various problems of manual scribing. The proposed RAS3DM can be widely applied in factories and laboratories.